"Tissues in a Dish": A Review of Organoids in Plastic Surgery. Issue 4 (29th April 2020) - Chinta, Malini S.; desJardins-Park, Heather E.; Wan, Derrick C.; Longaker, Michael T.
Abstract : Summary: Organoids are in vitro miniaturized organ models—or, colloquially, "organs in a dish." These 3-dimensional, multicellular structures are classically derived from pluripotent or multipotent stem cells. When guided by tissue-specific molecular factors, these cells exhibit self-organizing abilities that allow them to accurately recapitulate the architecture and function of the organ of interest. Organoid technology is a rapidly expanding field that endows researchers with an unprecedented ability to recreate, study, and manipulate complex biologic processes in vitro. When compared with standard 2- and 3-dimensional culture systems, which rely on co-culturing pre-established cell types, organoids provide a more biomimetic model with which to study the intercellular interactions necessary for in vivo organ function and architecture. Organoids have the potential to impact all avenues of medicine, including those fields most relevant to plastic and reconstructive surgery such as wound healing, oncology, craniofacial reconstruction, and burn care. In addition to their ability to serve as a novel tool for studying human-specific disease, organoids may be used for tissue engineering with the goal of developing biomimetic soft-tissue substitutes, which would be especially valuable to the plastic surgeon. Although organoids hold great promise for the field of plastic surgery, technical challenges in creating vascularized, multilineage organoids must be overcome to allow for the integration of this technology in clinical practice. This review provides a brief history of the organoid, highlights its potential clinical applications, discusses certain limitations, and examines the impact that this technology may have on the field of plastic and reconstructive surgery.